Hubungan Psikologi Spiritual Pendidikan Terhadap Fear of Missing Out (FOMO) Pada Mahasiswa di Perguruan Tinggi Agama Islam Negeri Kerinci - Aprilita, Tesha Dwi; Putra, Pristian Hadi (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The Fear of Missing Out (FOMO) phenomenon is defined as a form of social anxiety that arises when individuals feel left out of positive experiences enjoyed by others, especially through social media. In today's digital and modern era, the phenomenon of “Fear of Missing Out,” or FOMO, has become commonplace in everyday life, especially among college students. Students often find themselves in a period of life filled with stress, particularly regarding their mental health. The influence of religious psychology on FOMO among students highlights the complexity of the psychosocial challenges faced by students in today's digital and social media era. This study uses quantitative research methods with correlation tests and descriptive statistical approaches. The sample consists of 108 students at the Kerinci State Islamic University. This article explores the relationship between religious psychology and FOMO behavior among students, with the aim of identifying potential interventions and support that can help students in their use of FOMO and improve their well-being in an ever-changing digital environment.